Kompetensi Profesional Guru Sekolah Menengah Pertama Kabupaten Kendal - Anif, Sofyan; Sutama, S.; Prayitno, Harun Joko; Sukartono, S. (Universitas Muhammadiyah Surakarta, 2019)
The teacher has a vital and fundamental role as an agent of change in helping and guiding students in the process of changing from not knowing to knowing, not understanding to understanding, not mastering to mastering and so on. Such circumstances indicate that it is appropriate to improve the professional competence of teachers. The purpose of this study is to describe the professional competence of junior high school teachers. The research method used is qualitative with data collection techniques through observation, interviews and documentation. Data validation is done through triangulation, with analysis of data flow methods with the process: data collection, data reduction, then presented, followed by conclusions and verification. The results showed that the professional competence of teachers showed an average of 1.33 in poor condition. Specifically if related to teacher perceptions, it can be seen from the competencies about personality and competencies about carrying out tasks. Perspesi regarding personality is related to work discipline, work morality, loyalty, responsibility and human relations, while the perception of competence in carrying out tasks is related to work suitability andfluency in carrying out tasks.